2007
DOI: 10.1002/chin.200723094
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Investigation of Some Novel Phenyl Pyrazole, Azetidinone and Diazenyl Ethanone Derivatives of Benzofurans.

Abstract: Twenty title compounds such as (V), (IX), or (XI) are screened for their antimicrobial and antifungal effects. Some derivatives of type (IX), e.g. derivative (IXb), show significant activities. -(KUMAR, D. B. A.; PRAKASH, G. K.; KUMARASWAMY, M. N.; NANDESHWARAPPA, B. P.; SHERIGARA, B. S.; MAHADEVAN*, K. M.; Indian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…IR spectra were recorded on Shimadzu FTIR-8400s spectrophotometer. 1 H NMR and 13 C NMR spectra were recorded on Avance 300 spectrometer, and mass spectra were recorded on Shimadzu mass spectrometer. Elemental analysis was determined by using ThermoFinnigan CHNS analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…IR spectra were recorded on Shimadzu FTIR-8400s spectrophotometer. 1 H NMR and 13 C NMR spectra were recorded on Avance 300 spectrometer, and mass spectra were recorded on Shimadzu mass spectrometer. Elemental analysis was determined by using ThermoFinnigan CHNS analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…A literature survey showed that the acetanilide derivatives 2a-f were obtained through acylation of the appropriate amines with chloroacetyl chloride using different reaction conditions such as triethylamine, potassium carbonate, sodium acetate or pyridine in different solvents such as glacial acetic acid, dichloromethane, DMF or acetone. [43][44][45][46] In this study, the acetanilide derivatives 2a-f were synthesized with good yield using acetic acid and sodium acetate according to the method by Kumar et al 47 On the other hand, intermediates 4a and b were synthesized by reacting 2-pyrrolidinone 3a or 2-piperidinone 3b with malononitrile in dry benzene via condensation reaction. 48 These intermediates were conrmed by their melting points, as reported.…”
Section: Chemistrymentioning
confidence: 99%
“…2-Acetylbenzofuran (1) and 3-(benzofuran-2-yl)-1-phenyl-1H-pyrazole-4-carbaldehyde (2) [12] reacted in the presence of aqueous sodium hydroxide yielded the 1,3-disubstituted prop-2-en-1-one derivative 3. Bromonation of 3 with bromine in chloroform yielded 2,3-dibromo-1,3-disubstituted propan-1-one 4 in good yield.…”
Section: Chemistrymentioning
confidence: 99%